The Effectiveness of the Problem-Based Learning Model Assisted by Augmented Reality on Learning Outcomes of the Natural Sciences Subject of Plant Body Parts Material - Nova Dwiyanti; Novi Setyasto (Postgraduate, University of Mataram, 2025)
The use of learning models and media that are not in accordance with Permendikbudristek Number 16 of 2022 concerning process standards has an impact on low student learning outcomes. This study examines the effectiveness of the Problem-Based Learning model assisted by Augmented Reality on the learning outcomes of class IV of SD Gugus Pringgodani, Banyumanik District, Semarang City. This study is included in the type of experimental research with a quasi-experimental design in the form of Nonequivalent Control Group Design. This study uses a purposive sampling method to take samples from students of SD Gugus Pringgodani, Banyumanik District, Semarang City. In this study, Prince Diponegoro Islamic Elementary School class IV C acted as the control class and class IV D as the experimental class. Initial data analysis techniques include normality and homogeneity tests and final data analysis with t-tests and N-Gain tests. The t-test results obtained a sig value of 0.000 (sig. <0.05), so H0 is rejected and Ha is accepted. The N-Gain test output of the experimental class is 0.57 and the control class is 0.38, so it can be concluded that the Problem-Based Learning model assisted by Augmented Reality is more effective than the Problem-Based Learning model that is not yet in according to the syntax assisted by image media on the learning outcomes of science subjects in grade IV of SD Gugus Pringgodani, Banyumanik District, Semarang City.